2007
DOI: 10.1021/ja073115c
|View full text |Cite
|
Sign up to set email alerts
|

Length-Dependent Optical Effects in Single-Wall Carbon Nanotubes

Abstract: Among the novel chemical and physical attributes of single-wall carbon nanotubes (SWCNTs), the optical properties are perhaps the most compelling. Although much is known about how such characteristics depend on nanotube chirality and diameter, relatively little is known about how the optical response depends on length, the next most obvious and fundamental nanotube trait. We show here that the intrinsic optical response of single-wall carbon nanotubes exhibits a strong dependence on nanotube length, and we off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
203
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(221 citation statements)
references
References 23 publications
16
203
2
Order By: Relevance
“…91 Samples that have endured ultrasonic processing are expected to display shorter average lengths for large-diameter species, which we did not observe here, likely due to limited statistical data for (9,1) and (8,3) SWNTs. 137,156 In addition, unlike previous measurements performed for ensembles of nanotubes, 212 longer SWNT lengths did not correlate with brighter luminescence intensities, although direct comparison was again complicated by variations in the orientation of the SWNTs on the substrate with respect to the excitation polarization.…”
Section: Correlated Fluorescence and Topographycontrasting
confidence: 73%
See 2 more Smart Citations
“…91 Samples that have endured ultrasonic processing are expected to display shorter average lengths for large-diameter species, which we did not observe here, likely due to limited statistical data for (9,1) and (8,3) SWNTs. 137,156 In addition, unlike previous measurements performed for ensembles of nanotubes, 212 longer SWNT lengths did not correlate with brighter luminescence intensities, although direct comparison was again complicated by variations in the orientation of the SWNTs on the substrate with respect to the excitation polarization.…”
Section: Correlated Fluorescence and Topographycontrasting
confidence: 73%
“…It is also unclear how the QY varies with SWNT length, which is a subject of current debate. For example, Fagan et al have observed a strong dependence of fluorescence intensity on nanotube length 212 that is supported by another study showing an exciton diffusion length of ~90 nm along the SWNT. 116 These studies imply that the fluorescence efficiency for short SWNTs may lowered by efficient quenching of bound excitons at the cut ends of nanotubes.…”
Section: Single Molecule Fluorescence Quantum Yield Of Swntsmentioning
confidence: 77%
See 1 more Smart Citation
“…The first absorption peak of (4,4) (C 48 ) was located at 977.8 nm, and that of (5,5) (C 60 ) was at 937.5 nm. It had been observed in the experiment that the first absorption peak of (6,5) SWCNT was near 990 nm [11], which supported our calculation results. On one hand, the first absorptions for most of the doped SWCNTs compared with those of the pristine SWCNTs were redshifted (Table 2).…”
Section: Electronic Absorption Spectrasupporting
confidence: 91%
“…This duality depends on the diameter of the SWCNTs and arrangement of the hexagons [10]. Besides the electrical conductivities, a tunable optical property of the SWCNTs has been observed in Jeffrey's experiments [11]. In addition, the dispersed SWCNTs have also played an important role in the enhancement of the effective thermal conductivity of fluids [12].…”
Section: Introductionmentioning
confidence: 99%